Scale-up synthesis and characterization of 2,6-diamino-3,5-dinitropyrazine-1-oxide - Hai-bin Wang (Defence Technology, 2014)
2,6-diamino-3,5-dinitropyrazine-1-oxide (ANPZO), as an insensitive high explosive, with a high yield and excellent purity has been prepared at pilot plant scale by an improved method. The synthesized ANPZO is characterized by IR, laser granularity measurement, SEM and HPLC. The particle analysis revealed that the improved method could offer desired product with average particle size of 40 μm and high purity (>98.45%). The experimental parameters exhibited that the detonation velocity of the formulation based on ANPZO was higher than that of the corresponding TATB formulation. The DSC curve showed that the exothermic decomposition of the product occurred at the temperature between 300.5 °C and 360.4 °C. Furthermore, the sensitivity test suggests its safe nature towards mechanical stimulus.